On the Performance of Quasiorthogonal STBC with Relay Selection and Phase Rotation Techniques for Decode and Forward Cooperative Communications. (5th February 2013) - Sutthisangiam, Nikorn; Pirak, Chaiyod; Ascheid, Gerd
Abstract : The performance of quasiorthogonal space-time block code with relay-selection and phase-rotation techniques applied to cooperative communications for four communication nodes is investigated. Specifically, by applying relay-selection and phase-rotation techniques, a diversity gain of four can be achieved. In addition, a symbol error rate (SER) performance analysis with closed-form expression and power allocation are investigated and compared with simulation results. The results show that theoretical SER curves are close to the simulation results. In addition, a code rate of the proposed scheme is two times higher than ordinary cooperative communications. The computer simulation results also show a significant probability of error improvement of about 2.8 dB over the conventional decode-and-forward protocol.